Evaluation of Patients with Cockayne Syndrome - Hamit Acer; Gül Demet Özçora; Mehmet Canpolat; Muhammet Ensar Doğan; Zehra Filiz Kahraman; Sefer Kumandaş (Galenos Publishing House, 2024)
Cockayne syndrome (CS) is a rare, severe, genetic neurodegenerative disorder. To better understand the condition, this article aimed to discuss the clinical manifestations and prognosis of CS. This clinical study was a retrospective review of the medical records of patients diagnosed with CS between January 2010 and January 2020. A total of 9 patients (6 males, 66.7%; 3 females, 33.3%) from 7 families were enrolled in the study. The median age of the patients was 94 (4-186) months. Genetic confirmation of CS was obtained in 5 of the patients and ERCC8 mutations were identified in all patients who underwent genetic confirmation of the disease. On admission, 8 patients were found to have microcephaly 4 patients were admitted for psychomotor retardation, 3 for seizures, and two for walking disabilities. The diagnosis of patients with CS can be challenging due to the wide range of symptoms. In patients who are normal at birth but develop microcephaly during follow-up, physicians should consider CS in addition to metabolic diseases in the differential diagnosis.